Assessing the Effect of Short-Term Interval Training on Acceleration Ability and Anaerobic Power of Novice Sprinters - Prasenjit Paria; Amit Dhar; Ankur Biswas; Subhashis Biswas (OVS LLC, 2024)
Background. Acceleration ability and anaerobic power are critical determinants of sprinting performance, particularly for novice sprinters. Objectives. The purpose of the study was to examine the effects of a four-week interval training program on acceleration ability and anaerobic power among novice sprinters. Materials and methods. A within-subjects quasi-experimental design was used to fulfil the study's objectives. A total of fifteen participants (age: 20.5 ± 1.4 years) underwent baseline assessments of acceleration ability (50 m dash) and anaerobic power (Running-Based Anaerobic Sprint Test). The adopted progressive interval training protocol consisted of four weekly sessions conducted over a four-week period, focusing on striding, high knees, single-leg hops, curve sprints and double-leg jumps to enhance acceleration ability and anaerobic power. Results. Following the intervention, significant improvements were observed in acceleration ability over a distance of 10 m (pre: 2.14 ± 0.16 s, post: 2.02 ± 0.14 s, p < 0.05, Cohen's d = 1.02) and 20 m segments (pre: 3.47 ± 0.23 s, post: 3.32 ± 0.20 s, p < 0.05, Cohen's d = 0.78), indicating moderate to large effect sizes. However, no considerable enhancements were found in anaerobic power parameters (average power, maximum power, minimum power, fatigue index, relative peak power, and anaerobic capacity) at the post-intervention stage (p > 0.05). Conclusions. The study highlights the effectiveness of the interval training protocol in enhancing initial acceleration among novice sprinters, although it suggests a limited impact on anaerobic power within the study period. Further research should investigate the longer-term effects and tailored training approaches to optimize comprehensive sprint performance strategies.